Seasonal differences in Varroa destructor population growth in western honey bee (Apis mellifera) colonies - Jack, Cameron J.; de Bem Oliveira, Ivone; Kimmel, Chase B.; Ellis, James D. (Frontiers in Ecology and Evolution, 2023)
Varroa destructor is a major threat for apiculture worldwide. A successful approach to control this parasite must include the application of effective treatments at the correct time. To understand the effect that treatment timing has on Varroa populations at different seasons, we conducted an experiment using a dataset comprising two separate field trials over multiple years, both trials containing four apiary sites composed of 20 honey bee colonies across an area representative of north central Florida environments. Before the start of the season, colonies were treated with two acaricides simultaneously to bring the Varroa populations to ~0.25 mites/100 bees. Following treatment, we monitored the mite populations monthly via alcohol washes. Our results show that the temporal efficacy of Varroa treatments varies across seasons. We observed that it takes about 4-5 months after treatment in winter and spring for mite populations to return to the standard economical threshold (3 mites/100 bees). Nevertheless, there is a steeper increase in mite populations (< 3 months to exceed the economic threshold) after treating colonies in summer and fall. The level of infestation that leads to colony collapse and the rate of colony decline also varied by season. To our knowledge, this is the first study evaluating seasonal effects on Varroa population growth and the first model of Varroa population growth in Florida, USA. Our results serve as a foundation for Varroa treatment models, aiding beekeepers in the future as a part of a holistic approach to control this devastating honey bee parasite.